An investigation into the leaching behaviour of copper oxide minerals in aqueous alkaline glycine solutions - Tanda, B.; Eksteen, Jacques; Oraby, E. (Elsevier, 2017)
Copper oxide minerals are normally extracted by acidic leaching followed by copper recovery with solvent extraction and electrowinning. However, copper oxide deposits often containing large amounts of acid consumable gangue leads to a very high acid consumption. In addition, if the oxide deposit also contains precious metals and iron bearing minerals, significant (lime) neutralisation costs are incurred to establish the conditions for subsequent cyanidation, with concomitant production of gypsum, potential formation of silver-locking jarosites and potential gel formation when acids interact with layer silicate minerals. In this study, an alternative aqueous alkaline glycine system has been employed to evaluate the batch leaching behaviour of copper oxide mineral specimens of the minerals azurite, chrysocolla, cuprite and malachite. The effects of glycine concentration and pH were investigated at ambient temperature and atmospheric pressure. Glycine concentration and pH both had a major effect on the copper extraction. Complete extraction of copper from azurite was achieved in < 6 h when glycine to copper ratio was 8:1. However, further investigation established the optimum leaching conditions as being pH 11 and glycine to copper ratio of 4:1. Under such conditions 95.0%, 91.0%, 83. 8% and 17.4% of copper was extracted after 24 h from the azurite, malachite, cuprite, and chrysocolla mineral specimens respectively. While the dissolution rates of the copper oxide minerals are markedly slower than acid leaching, the selective dissolution of copper over acid-consuming gangue minerals shows much potential. It was shown through UV–Vis spectroscopy that dissolved copper is in the cupric state and forms a neutral copper-glycinate complex under alkaline conditions. The study has shown that copper extraction from malachite, azurite and cuprite in aqueous alkaline glycine solutions is fast, whereas Cu extraction from chrysocolla was found to be poor and slow.